Optimization of Oyster Mushroom Yield By Using Simplex-Centroid Mixture Design - Kasina, Martin Musembi; Koske, Joseph; Mutiso, John (Journal of Scientific Research and Innovative Technology, 2020)
Despite the increased recognition of the nutritional value of the Oyster mushroom, coupled with its ability to tolerate a wide range of climatic conditions, its production is still at infancy stage with low adoption rate in Kenya. The low uptake could be attributed to lack of skills for substrates preparations or cost of buying the substrates coupled with poor knowledge on its consumption benefits. The objective of this study was to optimize Pleurotus ostreatus (Oyster mushroom) yield by establishing the local suitable substrates mixture that maximized the yield in Machakos County, Kenya. To achieve this objective simplex-centroid mixture design was used. Based on the study findings there was a significant variability on the substrate compositions used under the study, which included sawdust, sugarcane baggase, star grass, euphoria and the cattle manure. Sawdust yielded the most under the pure blend at 1.1 kg per experimental unit while on the mixed blend sugarcane bagasse and sawdust produced the highest yield at 1.3 kg per experimental unit (1kg of dry substrate), giving 10% and 30% biological efficiency respectively. There was no pinning on the cattle manure and the euphorbia substrates hence they were eliminated at the screening stage. The mixture response was found to be more valuable than the pure blend responses then simplex- centroid mixture design to rightly proportion the substrates was recommended for improved oyster mushroom production. A further research on determining suitability of alternative locally found substrates which may be more cost effective and multiple response optimizations aimed at achieving maximal nutritional value and yield against minimal cost of spawns and substrates were recommended.
Keywords: Substrates; simplex centroids mixture designs; optimization